Pengaruh Gel Ekstrak Bawang Merah terhadap Jumlah Fibroblas pada Luka Ekstraksi Gigi Tikus Jantan Wistar - Aulia Rahmawati, Amilatul; Harijadi, Achmad; Kristanto, Yanuar; Asmarani, Yolanda Kartika (Fakultas Kedokteran Gigi IIK Bhakti Wiyata, Kediri., 2023)
Background: Tooth extraction is the procedure of removing the tooth and its roots from the socket and can cause the injury. Post-tooth extraction wounds requires tissue replacement through the wound healing process. Wound healing process after the tooth extraction can be assisted by administering herbal plants, such as onion which mostly contains flavonoids that can play a role in the wound healing process because they are useful as anti-inflammatory and antimicrobial. Purpose: This study aims to determine the effect of giving onion extract gel (Allium cepa L.) towards amount of fibroblast cells in the wound healing process after tooth extraction in male wistar rats (Rattus norvegicus). Methods: This study used an experimental laboratory design with a post test only randomized control group design in male wistar rats (Rattus norvegicus). The sample was divided into 4 groups, there are the control group and the treatment group which was given by onion extract gel with 0,06% of the concentration and decapitated on the 5th and 7th day. The tissue was taken and decalcified then stained with Haematoxylin Eosin (HE) then the fibroblast cells were observed and counted using a microscope. Results: Data were analyzed using the Oneway Annova parametric test, showing a significance value of 0.000 showed that there was a significant difference in the number of fibroblast cells between the 4 groups. The Tukey HSD test showing that each groups showed a value (p<0.05) so that all groups were different from each other and there are no group was not significantly different. Conclusion: Onion extract gel with 0,06% of the concentration has an effect on increasing the number of fibroblast cells thereby accelerating the wound healing process. Keywords: Tooth Extraction, Wound Healing, Fibroblast Cells, Onion Extract Gel (Allium cepa L.)